2020
DOI: 10.1016/j.bpj.2019.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Expression Transition of Cardiac Myosin Using Polarization-Dependent SHG Microscopy

Abstract: Detection of the transition between the two myosin isoforms aand b-myosin in living cardiomyocytes is essential for understanding cardiac physiology and pathology. In this study, the differences in symmetry of polarization spectra obtained from aand b-myosin in various mammalian ventricles and propylthiouracil-treated rats are explored through polarization-dependent second harmonic generation microscopy. Here, we report for the, to our knowledge, first time that aand b-myosin, as protein crystals, possess diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Sarcomeres of C. elegans exhibit progressive F I G U R E 6 A, Mean DIF computed with DFT based on Equation ( 8) and estimated with a fitting procedure based on trigonal symmetry's Equations ( 9), ( 17) and ( 18) for the same samples as disorganization, with less tight packing and some disorientation of myosin molecules with aging [3,4]. In addition, a very recent study [17] has observed that there is a transition of SHG modulation with respect to the laser polarization in rat ventricles myosin filaments from a cylindrical to trigonal symmetry line profile during aging. The obtained results are in accordance with our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcomeres of C. elegans exhibit progressive F I G U R E 6 A, Mean DIF computed with DFT based on Equation ( 8) and estimated with a fitting procedure based on trigonal symmetry's Equations ( 9), ( 17) and ( 18) for the same samples as disorganization, with less tight packing and some disorientation of myosin molecules with aging [3,4]. In addition, a very recent study [17] has observed that there is a transition of SHG modulation with respect to the laser polarization in rat ventricles myosin filaments from a cylindrical to trigonal symmetry line profile during aging. The obtained results are in accordance with our study.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have used PSHG measurements for the functional imaging of muscle cells and the in-vivo monitoring of conformational changes in myosin [15,16]. Moreover, structural modifications of cardiac myosin filaments have been detected, and the discrimination of a-and b-myosin in cardiac samples via PSHG was possible [17,18]. In the current work, we used PSHG imaging microscopy to measure aging-related myosin structural modifications in the striated muscles of C. elegans samples.…”
mentioning
confidence: 99%
“…NIR imaging is currently considered a well‐integrated option in intravital microscopy, since it can be easily deployed on point‐scanning laser systems, in conjunction with visible range laser lines that are adopted for confocal microscopy. The advantage of using NIR tuneable pulsed lasers relies on the possibility of visualising in‐depth fluorescent tissues 22 and to obtain, as a label‐free signal, the second harmonic generation (SHG) from biologically relevant non‐centrosymmetric structures such as collagen 23 and myosin 24 . Furthermore, in multiphoton microscopy, the excitation probability decreases very rapidly as function of the distance from the focal plane, conferring then an intrinsic spatial confinement to the generated fluorescence or label‐free (SHG) signal; indeed, the effective excitation volume is in the order of a femtolitre 25 …”
Section: Infrared Radiation Imaging and Spectroscopymentioning
confidence: 99%
“…SHG image contrast is proportional to the molecular structure and order of the myosin. Also, Yuan et al demonstrated that α- and β-myosin possess different symmetries that were observed under polarization-resolved SHG microscopy in a single-sarcomere line scan [ 42 ]. Again, the changes in the structure and physiological properties of myofibrils are investigated through the intrinsic SH signal [ 5 , 37 ].…”
Section: Introductionmentioning
confidence: 99%